PENERAPAN METODE TOPSIS DALAM SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN PEMENANG LOMBA DESA/KELURAHAN - Septilia Arfida (Jurnal Informatika, 2013)
Empowerment of rural / urban, institutional strengthening needs to be done, increased motivation and self-help mutual aid society in rural / urban . So as to assess the success of rural development / urban, race needs to be done in a focused, coordinated, integrated and sustainable. Assessment is done by comparing the race developmental level two (2) years based on the profile data villagers/villages in accordance with the assessment indicators. Decision support system race village/sub can overcome the weaknesses and shortcomings of the implementation of the previous rac. This new system can be done quickly, open and competitive despite the relatively large amount of data but the accuracy of the calculation and reporting can be achieved as much as possible. So the time efficiency in the execution and completion of the report will be better. Decision support applications to determine the winners of the Village/Village calculation method using Technique for Order Preference by Similarity to Ideal Solution (TOPSIS).Keywords : Decision Support System, TOPSIS, Determination of Winners Rural / Urban